Via colinérgica anti-inflamatória: um alvo terapêutico no curso da mucosite intestinal induzida experimentalmente por 5-fluorouracil - Mendes, Tiago Santos (2019)
The interrelation between the enteric nervous system and the inflammatory process in the pathogenesis of morphofunctional changes caused by 5-Fluorouracil (5-FU) was analyzed. Male Swiss mice weighing 25-30g from the Federal Center of Ceará under protocol 74/2014 received a single dose of 5-FU (450mg / kg-ip) and were treated with neostigmine (NEO-80μg (kg -1), or pyridostigmine (PIRO-2mg / kg-ip) for 3 days starting 1 day before induction with 5-FU were divided into 6 groups: saline control (S), intestinal mucositis (5FU), saline + pyridostigmine (P), saline + neostigmine (N), 5FU + P and 5FU + N. The cervical displacement sacrifice followed 3 days (3d) and 15 days (15d) after administration (inflammatory and postinflammatory phases, respectively), 1cm of the ileal segment was obtained for histopathological and morphometric analysis, myeloperoxidase (MPO), glutathione GSH), malondialdehyde (MDA), IL-1β dosage, acetylcholinesterase activity (AChE), immunohistochemistry for M3 receptors, immunofluorescence for Hu C / D-ChAT, functional parameters of gastric emptying (EG), intestinal transit of the contractile parameters by electrostimulation with voltage curve (10 to 80v) and frequency curve (1 to 32Hz). For statistical analysis it was considered p <0.05, where data were expressed as median for histopathological and morphometric analyzes and mean ± standard error of the mean. In the results of Histopathology we observed the following: (S: 0 (0-1); 5FU 3d: 2 (2-3) *; P: 0 (0-1); N: 0 (0-1); 5FU + P (2-1), 5FU + N: 1 (1-2), 5FU 15d: 1 (0-1), 5FU + P: 1 (0-1), 5FU + N: 1 (0-1). In MPO (S: 3.24 ± 0.31, 5FU: 17.92 ± 2.01 *, P: 3.37 ± 0.69, N: 4.18 ± 0.18, 5FU + P: 16 , 48 ± 3.06 *, 5FU + N: 4.98 ± 0.93 # UMPO / mg tissue), showed difference by increased enzymatic activity in the 5-FU group compared to the S group. (S: 179.88 ± 15.5; 5FU: 648.4 ± 51.6 *; N: 45.38 ± 9.3; 5FU + N: 201.18 ± 28.3 * nM / μg protein / min). In the results of GSH (S: 199.9 ± 8.71, 5FU: 120.9 ± 6.77, P: 107.5 ± 9.38, N: 203.1 ± 4.9, 5FU 376.4 ± 70.98, P: 593.5 ± 100.9, N: 597.385 ± 97.3, FU+P: 297.5 ± 80.58, 5FU+N: 839.43 ± 100.93 5FU+N: 118.8 ± 7.93# NP-GSH μg), the results of AChE activity (S: 971.3 ± 210.9; 5FU: 376,4 ± 70,98; P: 593,5 ± 100,9; N: 597,385 ± 97,3; FU+P: 297,5 ± 80,58; 5FU+N: 839,43 ± 100,93# nM/µg de proteína/min.). In the MDA results, we obtained: (S: 12.5 ± 1.31; 5FU: 29.12 ± 2.8*; P: 11, 3 ± 1.69; N: 13.48 ± 0.18, 5FU+P: 11.48 ± 0.06%; 5FU + N: 11.58 ± 1.43# nMol/g tissue). In the results of the immunohistochemistry M3: (S: 41.87 ± 6.41; 5FU 3d: 78.93 ± 4.57*; 5FU 15d: 76.24 ± 5.53* M3 receptor / mm²) and immunofluorescence in neurons immunoreactive myenteric plexus for HU C/D and cholinergic immunoreactive neurons for ChAT we found a significant relation in the 5FU group: (S: 66.6 ± 2.1; 5FU 3d: 80.3 ± 3.7*%). In contractility, hypercontractility was observed in the ileum of the animals of the 5FU group, tested with electrostimulation and pharmacologically with Acetylcholine and carbachol. On the 15th day after treatment with 5-FU the alterations found in the inflammatory analyzes were reestablished. However, a significant delay in gastric emptying and gastrointestinal transit remains. We can suggest from these results that the alterations in gastrointestinal motility observed by this study and described in the literature are by a decrease in AChE activity in the inflammatory and persistent period in the postinflammatory period, with that the cholinergic anti-inflammatory pathway has potential for therapeutic target without significant changes in inflammatory parameters.